2021
DOI: 10.1016/j.arthro.2021.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Monitoring Tendon and Muscle Recovery After Rotator Cuff Repair Using Diagnostic Ultrasound Demonstrates that Early Repair is Beneficial for Many Patients With Reparable Tears

Abstract: Rotator cuff repair is performed to effect healing of the enthesis; to restore shoulder comfort, strength, and function; to prevent tear propagation; and to prevent progression of atrophic muscle changes (fatty degeneration, fatty infiltration, and fatty atrophy) that eventually occur. Non-retracted and moderately retracted rotator cuff tears usually heal after repair, and muscle atrophy may recover over time. It follows that early rotator cuff repair is beneficial for many patients with chronic but reparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It does not return to normal strength or girth. Several studies [13][14][15][16] of chronic rotator cuff and Achilles tendon tears have demonstrated how this fatty atrophy is a risk factor for failure of primary repair.…”
Section: Possible Concerns Future Of the Techniquementioning
confidence: 99%
“…It does not return to normal strength or girth. Several studies [13][14][15][16] of chronic rotator cuff and Achilles tendon tears have demonstrated how this fatty atrophy is a risk factor for failure of primary repair.…”
Section: Possible Concerns Future Of the Techniquementioning
confidence: 99%